RA04.03: MINIMALLY INVASIVE ESOPHAGECTOMY IN THE LEFT LATERAL DECUBITUS POSITION. (14th September 2018) - Otsuka, Koji; Goto, Satoru; Ariyoshi, Tomotake; Yamashita, Takeshi; Motegi, Kentaro; Kato, Rei; Kohmoto, Masahiro; Saito, Akira; Date, Hiromi; Yamazaki, Kimiyasu; Aoki, Takeshi; Murakami, Masahiko
Abstract: Background: We initially performed minimally invasive esophagectomy in a left lateral decubitus position through 5 ports in 1996, and we have now treated over 900 cases using this approach. This position has many benefits, but it also has some drawbacks. We were able to operate with good results after we introduced artificial pneumothorax with CO2 insufflation in 2010. We investigated the short- and long-term outcomes of thoracoscopic surgery for esophageal cancer in the left lateral decubitus position at our institution. Methods: From 1996 to 2016, 807 esophageal cancer patients were treated with minimally invasive esophagectomy in the left lateral decubitus position at our hospital. We compared the 289 cases treated in the early period (1996–2005) and 518 cases treated in the late period (2006–2016), in which the procedure was standardized and operator training was established Results: The completion rate of thoracoscopic surgery was 99.5%, with the procedure switched to thoracotomy in only 3 patients in whom hemorrhage occurred. The mean intrathoracic operative time was 205.0 min, mean intrathoracic blood loss was 127.3 mL, and mean number of dissected mediastinal lymph nodes was 24.7. The postoperative complications were pneumonia (8.5%), anastomotic leakage (7.5%), and recurrent nerve paralysis (7.8%). The 5-year overall survival rate was 69.5%. Comparison of 289 cases treated in the early period (1996–2005) and 518 cases treated in the late period (2006–2016), revealed significant differences in mean intrathoracic blood loss (174.0 vs. 94.2 mL); number of dissected mediastinal lymph nodes (20.0 vs. 28.4); postoperative hospital stay (33.4 vs. 20.0 days, all P < 0.001); and postoperative anastomotic leakage (13.9% vs. 1.6%, P < 0.0001). In recent operation, we do not have recurrent laryngeal nerve paralysis and hoarseness after we take care of the micro anatomical layer, stretch and thermal damage of recurrent laryngeal nerve when we dissect the lymph node. Conclusion: These data indicate significant improvements in intrathoracic blood loss, number of dissected mediastinal lymph nodes, anastomotic leakage, and postoperative hospital stay, reflecting continued improvement of minimally invasive esophagectomy performed in the left lateral decubitus position at our institution. Disclosure: All authors have declared no conflicts of interest.